2001
DOI: 10.1111/j.1467-842x.2001.tb00319.x
|View full text |Cite
|
Sign up to set email alerts
|

School immunisation certificates — a review over time in a disadvantaged community

Abstract: Objectives: To compare proportions of kindergarten children in Auburn presenting School Immunisation Certificates (SIC) or other school‐entry immunisation documentation over time, and to examine the immunisation status of these children. Methods: Immunisation records of kindergarten children enrolled in all primary schools in the Auburn local government area were reviewed in 1994 and 1998. Results: Eight hundred and thirty‐three and 737 school entry records of children enrolled in kindergarten were reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A separate study to evaluate school entry requirements nationally would be useful, as State and regional studies have found problems with their effectiveness. 18,19 Despite many countries having a two-dose MMR schedule, data on the uptake of the second dose and reasons for non-compliance are sparse. 20 In this survey, reasons reported by parents for their child not having received MMR2 indicated that lack of parent and provider awareness of the scheduling of the second dose was the main f actor.…”
Section: Discussionmentioning
confidence: 99%
“…A separate study to evaluate school entry requirements nationally would be useful, as State and regional studies have found problems with their effectiveness. 18,19 Despite many countries having a two-dose MMR schedule, data on the uptake of the second dose and reasons for non-compliance are sparse. 20 In this survey, reasons reported by parents for their child not having received MMR2 indicated that lack of parent and provider awareness of the scheduling of the second dose was the main f actor.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of legislation requiring measles vaccination certificates to enroll children in an elementary school is to prevent and eliminate measles by enhancing the rate of booster vaccination. Many studies showed that the submission of vaccination certificate decreases the rate of outbreak of infectious diseases such as measles and mumps [11,12], and that the law requiring the submission of vaccination certificate enhanced the rate of measles booster vaccinations [13][14][15]. In the U.S., only 28 states and territories had laws for measles immunization by 1972 but by fall 2001, almost all (53 [98%] of 54) states and territories required a second dose of the measles vaccination upon students entry to school, at either the elementary school level, the middle school level, or both [16].…”
Section: Times Than Ones Of Immunization Bookletsmentioning
confidence: 99%